x;y nguyên => x+1; y-2 nguyên
=> x+1; y-2 \(\inƯ\left(2\right)=\left\{-2;-1;1;2\right\}\)
Ta có bảng
x+1 | -2 | -1 | 1 | 2 |
x | -3 | -2 | 0 | 1 |
y-2 | -1 | -2 | 2 | 1 |
y | 1 | 0 | 4 | 3 |
\(\left(x+1\right)\left(y-2\right)=2\)
\(\Rightarrow\left(x+1\right);\left(y-2\right)\inƯ\left(2\right)=\left\{\pm1;\pm2\right\}\)
TA CÓ BẢNG SAU:
\(x+1\) | \(-2\) | \(-1\) | \(1\) | \(2\) |
---|---|---|---|---|
\(y-2\) | \(-1\) | \(-2\) | \(2\) | \(1\) |
\(x\) | \(-3\) | \(-2\) | \(0\) | \(1\) |
\(y\) | \(1\) | \(0\) | \(4\) | \(3\) |
VẬY.........
HỌC TỐT
(x+1)(y-2)=2
Vì x;y là số nguyên => x+1;y-2 là số nguyên
=> x+1;y-2 E Ư(2)
Ta có bảng:
x+1 | 1 | 2 | -1 | -2 |
y-2 | 2 | 1 | -2 | -1 |
x | 0 | 1 | -2 | -3 |
y | 4 | 3 | 0 | 1 |
Vậy các cặp số (x;y) cần tìm là: (0;4) ; (1;3) ; (-2;0) ; (-3;1).